A review on complex event processing in RFID system - Yaacob, Siti Salwani; Mahdin, Hairulnizam; Saedudin, RD Rohmat; Ahmad Hijazi, Mohd Hanafi; Azmi, Mohd Sanusi; Rais, Nor Azlina (Indonesian Society for Knowledge and Human Development, 2018)
The motivation of this paper is to review some of the leading research issues encountered by current Complex Event Processing (CEP) techniques. General CEP system undoubtedly laid a certain degree of uncertainties due to some unforeseen reasons such as inaccurate measurements through network failures or unpredicted interference from the system failures. A variety of traditional to the most current techniques was disclosed with some features, which are rarely considered in typical CEP problems. Besides, this paper also discusses a broad review of modern and future solutions, including techniques beyond mainstreams in complex event processing. Based on the critical analysis of prior techniques and solutions, therefore, we further the research and propose a solution for a new type of event processing engine especially in RFID for future reference.